Personal protective equipment use and hand hygiene among physical therapists during the COVID-19 pandemic: an observational study (Research, Society and Development, 2022)
Objective: to describe personal protective equipment (PPE) use, hand hygiene and the association with biosafety training among physical therapists during the COVID-19 pandemic. Methods: this exploratory, observational, and transversal study was conducted in Brazil during the pandemic using an online self-administered questionnaire composed of the socio-demographic characteristics, PPE use, and hand hygiene. Statistical analysis was performed using Spearman’s correlation and logistic regression. Results: the most PPE used were long-sleeved lab coats (82.4%), face masks (81.4%) and closed shoes (79.1%). Most physical therapists washed hands before and after procedures (87.4%). Only 47.5% had biosafety training during the COVID-19 pandemic. Biosafety training was associated with medical apron (OR = 2.21. 95%CI = 1.08 to 4.52), isolation gown (OR = 2.71. 95%CI =1.09 to 6.75), long-sleeved lab coat (OR = 0.44. 95%CI = 0.22 to 0.87) and safety goggles (OR = 2.15. 95%CI = 1.21 to 3.84). Conclusion: although PPE use and hand hygiene are part of the Brazilian physical therapist routine, almost half of the assessed physical therapists had not performed biosafety training during the COVID-19 pandemic.